Synthesis and characterization of sensitive hydrogels based on semi- interpenetrated networks of poly 2-ethyl-(2-pyrrolidone) methacrylate and hyaluronic acid - Magalhães, Joana (2013)
Sensitive hydrogels attract interest due to their soft wet appearance and shape response to environmental variations. The synthesis and characterization of semi-interpenetrated hydrogels obtained by radical-induced polymerization of 2-ethyl-(2-pyrrolidone)methacrylate (EPM) in the presence of different concentrations of hyaluronic acid (HA) using N,N′-methylene-bisacrylamide or triethylene glycol dimethacrylate as crosslinker, followed by freeze-drying, are described. Polymeric systems were characterized by NMR, FTIR, SEM, TGA, and DMA. PEPMHA hydrogels' mechanical properties and swelling were found to be intimately related to HA concentration and crosslinker. The swelling response was assessed for temperature and pH variation in order to study the behavior of the hydrogels. We found that the presence of HA in PEPM polymeric systems induced a sensitivity to pH variation rather than temperature. Finally, the biocompatibility profile of the hydrogels was evaluated, using mesenchymal stem cells. Cell adhesion and proliferation results revealed the non-cytotoxicity of the systems. We estimate that PEPMHA hydrogels can be used for applications in tissue engineering and for the controlled release of bioactive compounds.